Hydroxycinnamic acids in the raw material of hybrid bearded iris - A. V. Krechun; O. O. Mykhailenko; V. M. Kovalov; Yu. V. Buidin; T. P. Osolodchenko (Zaporožskij Medicinskij Žurnal)
Representatives of Iris genus (Iridaceae) are widespread in almost all continents. According to the literature data, Iris species accumulate secondary metabolites such as flavonoids, isoflavonoids, xanthones, coumarins, hydroxycinnamic acids, saponins, tannins, vitamins, organic acids.